Effect of Tauge Extract and Starter Volume on the Quality of Liquid Fertilizer Whey Tofu - Hulyadi, Hulyadi; Indah, Dahlia Rosma; Suyanti, Ika (Jurnal Ilmiah IKIP Mataram, 2023)
Liquid organic fertilizer was a fertilizer in the form of a solution from the decay of organic materials. The combination of whey tofu and bean sprout extract with the addition of EM4 Starter can be processed into liquid organic fertilizer containing macronutrient nitrogen (N-total). The aim of the study was to determine nitrogen levels in liquid organic fertilizer whey tofu with variations in addition of extract of bean sprout and EM4 starter. This research method used Completely Randomized Design (CRD) with two factors, namely factor 1: volume of bean sprout extract (X) (X1 = 250 mL, X2 = 500 mL, X3 = 750 mL) and factor 2: volume Starter EM4 (Y) (Y1 = 5 mL, Y2 = 10 mL, Y3 = 15 mL). The results showed that the highest N-total was found in the treatment of X3Y1 which was 0.13% and the lowest level in the treatment X1Y3 was 0.05%.